Analytical study on social change in Tunisia from the pre-colonial period to Arab spring - M. G. Almheiri, Hamda Ghalib; Shuriye, Abdi Omar (Center for Promoting Ideas (CPI), USA, 2018)
There are natural forces of circumstances that control human system; inclination of change in man is very high and quick, however, occurrence of change has become constant and unchanging nature of life. In fact, that has become permanent phenomenon in human society. What are the components that changes in man’s life, behavior and characters, dogmas and beliefs, customs, norms and values, or all together? This research aims to provide an answer to the above question, through the study of radical socio-political changes in Tunisia from Precolonial Period until 2011 Revolution. Tunisia which is one of the most beautiful society, and the model of profound radical change at times, such as the revolution that sparked the Arab Spring (al-Raī’u al-‘Arabī) which is expected to change the Arabs world in twenty years or more, and in another time, an example of gradual change that takes a long time, as it happened during the time of independence and Bourguiba’s negotiation with the French colonists. In fact, Tunisia is claimed to be considered as the citadel of the West and the model that all the countries of the South must adopt and follow. This research has revealed that the phenomenon of radical change has occurred twice in Tunisia after its independence in 1956: first: when Habib Bourguiba issued the family code after four months from the independence, in which he abolished the legitimate provisions that related to religion and faith of the citizens by the force of law, and consequently followed by the series of decisions until the end of Bin Ali's reign, secondly: when Bu’azīzī set fire on himself, in fact as if he set the whole Arabs world ablaze. The research has figured out that Tunisia has been a pioneer in many fields, including its leadership in the establishment of the first educational institution in the sense of the university - Zaytuna University, it also pioneered the application of a new concept in the ideological war waged against the Islamists; policy of the sources drains which has become an exemplary strategy in the global war on the terrorism, as well as its application to finance, liquidation and others. The research confirmed that there are some symbolic community titles and ranks such as mysticism leaders, chief Shūrā of al-Mālikiyyah Council, first Imam of al-Zaytūnah Mosque, representing the moral weight in Tunisian society and playing vital roles in the community as well, especially in reconciling and bringing people of different segments in the society together on the public interests. In addition, the public Awqāfroles were also very essential, where its activities did not only limit to the Tunisian citizens but there were also allotted amount to the two Holy Mosques (Makkah and Madinah Mosques). The research concluded that the change occurs in any given society through one of these ways: law, principle of education and force, and for different purposes, including: Human need for dignity and personal respect, social need for justice and political need for freedom. What usually changes in man is conduct, by changing the values governing behaviors, through the interference in people’s identity, language and religion. In a nutshell, there is a definite effect between the system adopted by the authority and the impact of this system on the societal, economical and moral structures.